PHONOSEMANTIC UNIVERSALS IN L2 VOCABULARY ACQUISITION: EMPIRICAL EVIDENCE FROM THE ODAM TILI FRAMEWORK AND IMPLICATIONS FOR SECOND LANGUAGE TEACHING - Mahmudjon Kuchkarov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Second language (L2) vocabulary acquisition has long been treated as a process of  arbitrary  form-meaning  mapping,  following  the  Saussurean  principle  of  the arbitrariness of the linguistic sign. This article challenges that assumption by presenting empirical and cross-linguistic evidence from the Odam Tili (Human Language) theory developed  by  Dr.  Mahmudjon  Kuchkarov.  Drawing  on  a  longitudinal  multi-site experimental dataset collected from 26 volunteers of diverse racial, gender, and age backgrounds  across  three  phases  —  Fergana,  Uzbekistan  (2003);  New  York,  USA (2011); and Orlando, Florida, USA (2017)  — and applying a phono-signosemantic analytical  framework,  the  study  demonstrates  that  specific  phonemes  emerge systematically under defined biomechanical and environmental stimuli: /h/ as an index of physical load and hand agency (76% consistency across sites); /a/ as the universal phoneme of pain, distress, and biological origin; /o/ as the phoneme of long-distance projection (18% predominance over /a/ in competitive shouting trials); /t/ as the index of large-object impact (81%); /tʃ/ as the index of small-object impact (78%); and /s/-/ʃ/ as  sibilant  indices  of  smooth,  sliding  movement  (63%/37%  in  snake-association surveys). Cross-linguistic analysis demonstrates that these phonosemantic mappings are preserved in the lexicons of typologically distinct languages — including English, Uzbek, Russian, Hebrew, and Arabic — and in the visual forms and sequencing of major world writing systems. The article argues that these findings have direct and significant  implications  for  L2  vocabulary  teaching,  phonological  awareness instruction, cross-linguistic transfer facilitation, and the design of phonosemantically-informed L2 curricula, particularly for Eurasian learners of English.